Eksperimentasi Audio Spasial sebagai Material Struktural dalam Komposisi Musik ‘Aok Bah’ - Barata Gabrie Justitio; Puput Pramuditya; Haris Natanael Sutaryo (Institut Seni Indonesia Denpasar, 2026)
Purpose: The purpose of this research is to explore spatial audio concepts as an artistic strategy in music composition, specifically to create immersive listening experiences. This study specifically aims to test spatialization strategies as musical structures, which are organized based on considerations of timbre, register, and instrument organology. Method: This research was conducted through an experimental approach, utilizing the Higher-Order Ambisonics (HOA) system and Panoramix software. These systems were employed as the primary tools to test and manage spatialization strategies as structural musical elements during a live performance. Result and Discussion: The results of the study show that spatial audio techniques do not merely function as supplementary or additional effects. Instead, they can be fundamentally integrated as primary material and structural elements within a music composition, allowing for a more comprehensive perception of depth and height. Implication: These findings open new opportunities in contemporary music composition practices, where space is no longer just a passive container for sound but functions as an active and fundamental part of the musical process itself.